PENGARUH PENGGUNAAN GADGET (SMARTPHONE) TERHADAP ASPEK PERKEMBANGAN EMOSI DAN SOSIAL SISWA KELAS TINGGI PADA SD NEGERI 50 KOTA TERNATE - Nanda Yustika Suci; Ridwan Jusuf; Pamuti Pamuti (Universitas Khairun, 2021)
This study aims to determine the Effect of Using Gadgets (Smartphones) on Aspects of Children's Emotional and Social Development at SD Negeri 50 Ternate City. The method used in this study is quantitative survey with Cross Sectionalapproach. The population used in this study was students of SD Negeri 50 Ternate City aged 9-12 years with a total of 35 students while for the samples used in this study were students of SD Negeri 50 Ternate City aged 9-12 years with a total of 32 students. Sampling techniques used are Stratified Random Sampling. The variables in this study consisted of independent variables (X) the use of gadgets (smartphones), dependent variables (Y1) emotional development and dependent variables (Y2) social development. To obtain data in this study, questionnaires /questionnaires were distributed to students 9-12 years old. Questionnaires / questionnaires in this study using guttmannscale, with the form of positive and negative statements as many as 18 items. Then data analysis techniques using univariate and multivariate data analysis. Based on the results of the study using univariate data analysis obtained the use of gadgets (Smartphones) by 50% and emotional and social development by 56% while for the results of data analysis using manova test obtained significant values of 0.000 where 0.000 < 0.05 means H0 (reject) and H1 (receive). Thus, it can be concluded that the influence of the use of gadgets (smartphones) on aspects of emotional and social development of children.